APPRAISAL KEBERLANJUTAN MULTIDIMENSI PENGGUNAAN LAHAN UNTUK SAWAH DI KARAWANG - JAWA BARAT - Widiatmaka Widiatmaka; Khursatul Munibah; Santun R.P. Sitorus; Wiwin Ambarwulan; Irman Firmansyah (Jurnal Kawistara, 2015)
Indonesian national food sovereignty is very dependent on the supply of rice from paddy fields in Java Island. Various factors influence the farmer’s decision to continue using his farm. This study aims to analyze the sustainable use of paddy field, determinant factors and strategies for improving sustainability. The study was conducted in Karawang Regency, one of the centers of rice production in West Java. The methodology used is a multi-dimensional scaling (MDS) using 43 attributes of 5 dimensions (ecological, social, economical, technological and legal and institutional dimension). Against the sensitive attribute analysis resulting from MDS, a prospective analysis was conducted to determine the key factors of sustainability. Priority policies for improving sustainability are developed based on the location of the key factors in the prospective diagram. The research results showed that the land utilization for paddy field in Karawang is actually less sustainable. Increasing the sustainability can be done through intervention and improving performance, preferably on sensitive attributes resulting from leverage analysis, covering 16 attributes. Priority policies is directed in the 5 key factors resulting from prospective analysis. Policies suggested are the tightening of new permits for building, strict implementation of the official spatial land use planning and delineation of agricultural land for sustainable food crops, counseling the community, revitalizing the role of BULOG, provision of subsidies as well as capital assistance to farmers.